Investigation of Helio-geo-physical and Meteorological Factors for Cardiovascular Disasters during Summer (2002) in Saint Petersburg - Olga Stupishina; Elena Golovina; Sergei Noskov; Gennady Yeremin (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
This chapter investigates the helio-geo-physical and meteorological factors variations those were matching the different cardio-events. There is also increasing evidence that seasonal climatic factors can affect the presentation of cardiovascular diseases. The events were recorded by 6 medical institutes (state establishments) of Saint Petersburg. The results highlight the significance of solar radiobursts impacts, daily fluctuations in the geomagnetic field, and shifting atmospheric pressure systems in creating hazardous conditions for individuals suffering from cardiac arrests. Alternative safe environmental conditions are also displayed for such individuals.